Examining Cigar Pack Quantity Purchases by Cigar Type in the United States Between 2014 and 2017 - King Jensen, Jessica L; Cornacchione Ross, Jennifer; Rebentisch, Kayla; Delnevo, Cristine D; Azagba, Sunday (Nicotine & tobacco research, 2023)
Abstract Introduction We examined whether the proportion of cigar pack quantity usually purchased differed between 2014 and 2017 in the United States. Methods Data are from waves 1 and 4 of the Population Assessment of Tobacco and Health Study. The proportions of pack quantity purchases between waves for premium cigars, large cigars, cigarillos, and filtered cigars for 10-pack quantities (singles, 2-packs, 3-packs, 4-packs, 5-packs, 6–9-packs, 10-packs, 11–-19-packs, 20-packs, ≥21 packs) were compared using Z-tests. We used multivariable linear regressions to examine factors associated with pack quantity. Results For premium cigars, most adults purchased singles, with 84.4% in 2014 and 88.7% in 2017. For large cigars, single purchases increased from 46.2% to 62.7% (p < .00001). Two-packs also increased, 3.1% to 10.2% (p < .00001), while 5-packs, 6–9 packs, 10–19-packs, and 20-packs decreased. For cigarillos, singles purchases increased from 51.9% to 57.5% (p = .0002). Two-packs also increased, 8.8% to 19.6% (p < .00001), while 3-packs, 4-packs, 5-packs, and 20-packs decreased. For filtered cigars, the most prevalent pack quantity shifted from 20-packs in 2014 (62.6%) to singles in 2017 (36.7%). Singles, 2-packs, 3–4-packs, and 5-packs increased while 11–19-packs, 20-packs, and ≥21 packs decreased. Days used were positively associated with pack quantity purchase for all cigar types in 2017, while the price was positively associated with premium cigar purchase. Conclusions Between 2014 and 2017, the proportion of consumers who purchased singles remained at over 80% for premium cigars and increased for other cigars. Continued monitoring of use behaviors, including pack quantities by cigar type, is needed as the market and policy landscapes continue shifting. Implications Single cigar purchases are prominent across cigar types. Five-packs and 20-packs were the second most common pack quantities across cigar types, with relatively low proportions for other pack quantities. These findings suggest adults consuming premium cigars consistently prefer singles, a pattern that was found across cigar types. However, when considering purchases made online, premium cigars are widely purchased in larger pack quantities. Age and race were associated with purchase for some cigar types at some years, days used were associated with the purchase quantity in 2017 for all cigar types, and price was positively associated across time periods for only premium cigar purchases. Thus, the factors associated with cigar pack quantity purchase remain unclear. As the cigar policy landscape shifts, continued monitoring of the purchase behaviors by cigar type will be important to better inform future cigar policies.